Fall Prevention: Staying Active - Sergio Romero (EDIS)
A decrease in your level of physical activity, and a loss of balance and flexibility can increase your chances of falling. Other factors that may influence your risk of falling are poor vision, lack of strength, and hazards around the home such as poor lighting and cluttered walkways. This document includes exercises that can help you maintain or improve your balance, strength, and flexibility. Talk to your health care provider before starting any exercise program. This document is FCS2232, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: November 2000. Revised: April 2005.